Design of Home Made Lyophilized Serum as a Control Material for Internal and External Quality Control in Clinical Laboratories - Anik Handayati (Humanistic Network for Science and Technology (HNST), 2022)
Important control materials are used to achieve laboratory test quality. Control materials can be obtained from commercial serum or can be made independently in the form of pooled serum. Control materials commonly used in clinical laboratories are commercial control materials in lyophilized form. However, the price is quite expensive, so it is less efficient to use in laboratories where the average number of examinations is small. Homemade lyophilized control agents can be used as an alternative to expensive factory controls. This study aims to analyze the stability of homemade lyophilized serum as a control material for the parameters of glucose, uric acid, cholesterol, triglycerides, BUN, creatinine, SGOT and SGPT stored for 7 months. This research was an experimental study with a time series research design conducted at the Clinical Chemistry Laboratory, Department of Medical Laboratory Technology, Poltekkes Kemenkes Surabaya, in January 2022 to September 2022. Blood serum was processed using the freeze dry technique to obtain a lyophilized form. Lyophilized serum was stored at 2-8°C in the freezer, dissolved using aquabides and checked every month, for 7 months. The results of glucose, uric acid, SGOT, SGPT, creatinine, cholesterol, and triglyceride tests did not cross the CV line (CCV). The Levey Jennings graph shows that the results of glucose, uric acid, SGOT, SGPT, creatinine, BUN, cholesterol, and triglycerides were in the mean ± 2 SD and did not follow Westgard's law restrictions, meaning that the results of homemade lyophilized serum were well controlled (in control) for 7 months of storage. It can be concluded that the homemade lyophilized serum is stable over 7 months of storage.